Development of species‐specific multiplex real‐time PCR assays for tracing the small pelagic fishes of North Pacific with environmental DNA. Issue 3 (14th January 2022) - Wong, Marty Kwok‐Shing; Nobata, Shigenori; Ito, Shin‐ichi; Hyodo, Susumu
Abstract: Environmental DNA (eDNA) has become a popular non‐invasive method to study the presence of organisms in the environment. To study the ecological behavior and migration routes of small pelagic fishes that are difficult to trace with traditional capturing methods, we developed multiplex real‐time PCR assays to measure the eDNA of chub mackerel, blue mackerel, Japanese jack mackerel, Japanese anchovy, Japanese sardine, and Pacific saury. To test the validity, eDNA samples collected from the water near fisherman set nets in Northeast Japan between 2018 and 2019 were analyzed. Warm‐climate species including blue mackerel, jack mackerel, and anchovy were prominent in autumn, while cold‐climate species such as chub mackerel and sardine were richly present in winter. Pacific saury is an off‐coast species and was not detected in the coastal set net area. The eDNA data were partially correlated to the fishery catch records, suggesting that the eDNA quantities are relevant to the biomass of the fish schools, and our PCR assays can quantify the biological traces left by the small pelagic fish schools. Different patterns of eDNA occurrence were observed between the chub and blue mackerels, indicating that the specificity of the multiplex assay is applicable to field samples to measure the presence of the two closely related species separately. The methods are useful to evaluate the eDNA samples collected from the open water in the North Pacific to elucidate the life cycles and monitor the sustainability of the small pelagic fishes, which not only are important food sources, but also carry a role in the Japanese food culture. Abstract : Multiplex qPCR assays for 6 types of small pelagic fishes were developed to measure environmental DNA from open water to infer the occurrence of fish schools. The method sensitivity and specificity were tested using field samples obtained from fisherman's set nets. The developed method paves a way to trace the ontogenetic migration of small pelagic fishes in the North Pacific.